Improving the Professional Education of Accountants for the Effective Operation of the Economic Security System at Company Level - Pylypenko, O. І.; Yurchenko, O. А. (Statistics of Ukraine, 2020)
The effective company management involves the accounting of data about the likely misstatement or abuse that may impair the economic security of a company in the future. The current situation determines new requirements for the training of accountants, in particular as regards their knowledge of the effects of internal and external threats to the economic security. The study deals with the development of proposals to revise the requirements for accountants' qualifications in order to increase the accountant’s focus on enhancing the economic security of a company. The accountant’s activities have undergone structural change in the current business conditions. The accountant’s competencies on monitoring of the internal and external environment of a company lay the basis for providing reliable information about internal business processes and external environment to manage risks and prevent threats to the economic security of a company. The accountant may be entrusted with the functions of forming an accounting and analytical data set to facilitate control procedures and ensure the implementation of measures to achieve the economic security of a company. A review of the current content of professional education programs for Bachelor and Master training in the specialty “Accounting and Taxation” reveals that that neither scopes nor content of these programs are capable to ensure the competence of these professionals in issues of economic security at company level. It is proposed that professional education programs for Master training in the specialty “Accounting and Taxation” should include the discipline “Accounting and economic security of the company”, which content is expected to complement and integrate the acquired knowledge, and to build the competencies, skills and abilities for carrying out analytical research based on reporting and primary data, required to ensure the economic security of a company, forecast its performance and develop future business strategies. Teaching of this discipline will help improve the quality of the professional training of accountants and enhance the level of their retraining and qualification at all education levels.